Management Of Educational Financing Based On Efficiency And Accountability In Pesantren - Dina Sutiana; Elis Karwati Sri Mulyani; M Iksan Fahmi Nursyeha; Ikang Fauji; Ara Hidayat (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to analyze educational financing management at Pesantren Darul Qur’an Insan Cendekia Sukabumi by examining management functions, cost efficiency and effectiveness, as well as accountability and transparency in financial governance. The study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, document analysis, and focused group discussions involving pesantren leaders, financial administrators, and foundation representatives. Qualitative data analysis was conducted through data reduction, data display, and conclusion drawing, with data validity ensured through technique and source triangulation. The findings indicate that educational financing planning at the pesantren is conducted in a structured and participatory manner, involving both pesantren leadership and the foundation, and aligned with the institution’s vision, mission, and flagship programs. The implementation of educational financing follows a controlled fund disbursement mechanism, contributing to efficient and well-targeted use of financial resources. Financial efficiency is maintained through internal analysis and auditing procedures conducted before and after fund disbursement, as well as regular evaluations comparing budget realization with program targets. Financial supervision is carried out through routine monitoring and evaluation, supported by accountability reports and internal audits that strengthen transparency and institutional responsibility. Overall, the study demonstrates that the integration of management functions with principles of efficiency and accountability plays a crucial role in ensuring sustainable and trustworthy educational financing management in pesantren-based educational institutions.